2012
DOI: 10.1016/j.psyneuen.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Timing matters: Long term effects of adversities from prenatal period up to adolescence on adolescents’ cortisol stress response. The TRAILS study

Abstract: Results highlight the importance to take the timing of stress exposure into account. In addition to programming effects, pre/postnatal adversity interacts with childhood adversity in producing deviant cortisol levels. Puberty may be marked by a transition in how adversities affect the HPA-axis, with cortisol hypersecretion before age 11 and hyposecretion after age 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
140
3
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 41 publications
11
140
3
3
Order By: Relevance
“…The brain develops rapidly in childhood, and research from both animal and human models suggests that when an area of the brain is rapidly developing, that region is more sensitive to environmental threats (4,5,(17)(18)(19). Most studies examining the effects of multiple adverse experiences and developmental outcomes have disregarded the effect of timing of exposure (9,20). Studies are often cross-sectional or assess adverse exposures over a broad developmental period (e.g., before 18 y of age).…”
Section: Introductionmentioning
confidence: 99%
“…The brain develops rapidly in childhood, and research from both animal and human models suggests that when an area of the brain is rapidly developing, that region is more sensitive to environmental threats (4,5,(17)(18)(19). Most studies examining the effects of multiple adverse experiences and developmental outcomes have disregarded the effect of timing of exposure (9,20). Studies are often cross-sectional or assess adverse exposures over a broad developmental period (e.g., before 18 y of age).…”
Section: Introductionmentioning
confidence: 99%
“…Non-responders did not differ from responders in terms of sex; non-responders were slightly older (mean age 16.4 versus 16.1 year) [23].…”
Section: Study Participantsmentioning
confidence: 72%
“…This research also showed that childhood adversity was associated with neuroticism in adulthood. This was explained by the influence child adversity has on the emotional reactivity in brain functioning (Bosch, Riese, Reijneveld, Bakker, Verhulst, Ormel, & Oldehinkel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to incidents of interpersonal violence, the expectation is that certain primary personality factors will reflect changes, particularly those primary factors that are highly sensitive to environmental experience which has an impact on the hypothalamic-pituitary-adrenal (HPA) axis. The HPA axis and sympathetic-adrenal-medullary system are critical in promoting adaptive responses to stress, anxiety or fear, thus contributing to the regulation of the stress response (Bosch et al, 2012;De Kloet, Vermetten, Gouze, Kavelaars, Heijnen, & Westenberg, 2006).…”
Section: Introductionmentioning
confidence: 99%